MODERN APPROACHES TO THE PROBLEM OF IMMUNODEFICIENCIES IN CHILDREN - Nedelska, Svitlana; Samokhin, Ihor; Kriazhev, Oleksandr; Yartseva, Daria; Mazur, Victoriia (Eastern Ukrainian Medical Journal, 2024)
The course and development of infectious and inflammatory processes is often accompanied by immune system malfunction. A considerable number of lymphotropic viral infections can suppress immune system cells and increase the frequency of immunodeficiencies. This occurs, in particular, due to immunoproliferative, allergic, autoimmune diseases, etc.The paper aims to investigate the problem associated with childhood immunodeficiency diseases as of today.Immunodeficiencies are divided into two large groups by their origin: 1) phenotypic (secondary), which do not have genetic disorders; 2) genotypic (primary), which have genetic disorders. At the same time, immune disorders that arise during life in an organism with a normally formed immune system and are not associated with genetic abnormalities are diagnosed more often than primary immunodeficiencies. These disorders cannot represent an independent diagnosis because they are not an independent nosology.Acquired immunodeficiency can have the same clinical manifestations as primary immunodeficiency; in particular, it is manifested by frequent and prolonged infections. The so-called "opportunistic" infections may occur: these are diseases caused by microorganisms that are usually unable to cause a pathological process in a patient with a healthy immune system but can provoke diseases in people with suppressed immunity. Thus, paying special attention to the early diagnosis of congenital immunodeficiencies is necessary.Even though manifestations of immunodeficiency are not an indication for immediate treatment, doctors should monitor the changes that have been detected in specific immune system parameters.Conclusions. It is necessary to consider that any intervention in the immune system must have serious grounds. Usually, when eliminating the factors underlying acquired immunodeficiency, this condition resolves on its own.